The polarity of high-definition transcranial direct current stimulation affects the planning and execution of movement sequences - Jake J. Son; Tara D. Erker; Thomas W. Ward; Yasra Arif; Peihan J. Huang; Jason A. John; Kellen M. McDonald; Nathan M. Petro; Grant M. Garrison; Hannah J. Okelberry; Kennedy A. Kress; Giorgia Picci; et al. (NeuroImage)
Noninvasive brain stimulation of the primary motor cortex has been shown to alter therapeutic outcomes in stroke and other neurological conditions, but the precise mechanisms remain poorly understood. Determining the impact of such neurostimulation on the neural processing supporting motor control is a critical step toward further harnessing its therapeutic potential in multiple neurological conditions affecting the motor system. Herein, we leverage the excellent spatio-temporal precision of magnetoencephalographic (MEG) imaging to identify the spectral, spatial, and temporal effects of high-definition transcranial direct current stimulation (HD-tDCS) on the neural responses supporting motor control. Participants (N = 67) completed three HD-tDCS visits (anode, cathode, sham), with each involving 20 min of left primary motor cortex stimulation and performance of a simple/complex motor sequencing task during MEG. Whole-brain statistical analyses of beta oscillatory responses revealed stimulation-by-task interaction effects in the left primary motor cortex, right occipitotemporal, and the right dorsolateral prefrontal cortices. Broadly, anodal stimulation induced significantly stronger beta oscillatory responses in these regions during simple movement sequences, while neural responses to complex sequences were not affected by stimulation. En masse, these data suggest that the beta oscillations serving motor planning (i.e., pre-movement) are particularly sensitive to the polarity of noninvasive stimulation and that the impact varies based on the difficulty of the movement sequence.